2013
DOI: 10.1177/2045125313477103
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of methotrexate in precipitation of manic episode in bipolar affective disorder explored: a case report

Abstract: Bipolar affective disorder is characterized by recurring episodes of mania with or without, but commonly with, episodes of depression. It usually begins in adolescence and can cause enduring and substantial impairment if left untreated. It needs a long-term treatment with mood stabilizers to prevent relapses. Elevated or depressed mood relapses can be either primary or secondary. However, primary mood relapses can occur without a significant precipitating factor, more often tending to occur following stressful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…In the treatment of psoriasis, this described mechanism translates into the apoptosis of activated T cells, thereby restricting epithelial hyperplasia, a characteristic feature of the disease. [44] [45] The psychiatric side effects of methotrexate treatment are rare. In the literature, cases of psychosis and exacerbations of bipolar disorder have been described.…”
Section: Methotrexatementioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of psoriasis, this described mechanism translates into the apoptosis of activated T cells, thereby restricting epithelial hyperplasia, a characteristic feature of the disease. [44] [45] The psychiatric side effects of methotrexate treatment are rare. In the literature, cases of psychosis and exacerbations of bipolar disorder have been described.…”
Section: Methotrexatementioning
confidence: 99%
“…The authors of the case report identified the use of methotrexate as the most likely cause of the exacerbation of bipolar disorder. [45] Psoriasis is a condition that can significantly impair the quality of life, leading to anxiety, depression and lower self-esteem. A study involving 60 patients with psoriasis, treated either with methotrexate or biologic therapy, utilized the Beck Anxiety Inventory, Beck Depression Inventory and Dermatology Life Quality Index to assess their psychological well-being.…”
Section: Methotrexatementioning
confidence: 99%
“…After readjustment of antipsychotic therapy, symptoms subsided within 15 days. Table 2 [17,[81][82][83][84][85][86][87][88][89] summarizes chemotherapeutic agents associated with similar presentations.…”
Section: Chemotherapy-induced Mania: Should We Use Mood Stabilizers?mentioning
confidence: 99%
“…Показано, что все эти препараты могут давать нейропсихиатрические ПЭ, в частности, депрессивные и тревожные состояния [de Oliveira Ribeiro NP et al, 2013]. Описан случай провокации маниакального состояния метотрексатом [Hariram J, Jegan Y, 2013].…”
Section: иммуносупрессоры цитостатического рядаunclassified
“…Патофизиологические механизмы депрессогенного влияния иммуносупрессоров цитостатического ряда могут включать в себя прямое нейротоксическое действие (угнетение нейрогенеза и способствование апоптозу нервных клеток), и, в случае метотрексата, также угнетающее влияние на активность ферментов фолатного цикла, что приводит к повышению уровня гомоцистеина, нарушению синтеза тетрагидробиоптерина (BH4) и, как следствие, нарушениям в биосинтезе моноаминов, кофактором для некоторых стадий которого BH4 является [Hariram J, Jegan Y, 2013].…”
Section: иммуносупрессоры цитостатического рядаunclassified